High Performance Liquid Chromatographic Determination of Carboplatin in Injections - Agrawal, G.P.; Shenoy, G.; Ghosh, A.; Bhat, K.; Prabhu, L. (Asian Journal of Chemistry, 2011)
The present study describes the development and validation of a stability indicating reverse phase HPLC (RP-HPLC) method for the analysis of carboplatin, an anticancer drug, in injection dosage forms. The proposed RP-HPLC method utilizes Inertsil amino, 250 mm × 4.6 mm i.d., 5 μ column (at ambient temperature), isocratic run (using acetonitrile and water as mobile phase), at a flow rate of 2.0 mL min-1 and UV detection at 230 nm for analysis of carboplatin. The reported method is linear. Carboplatin was exposed to acidic, alkaline, oxidative, thermal and photolytic stress conditions- and the stressed samples were analyzed by the proposed method. Chromatographic peak purity results indicated the absence of co-eluting peaks with the drug peak, which demonstrated the specificity of assay method for estimation of carboplatin in presence of degradation products. The proposed method can be used for routine analysis stability testing of carboplatin in quality control laboratories.